Motion Analysis of Long-Distance Drive in Woodball Athletes - Irawan, Fajar Awang; Toma, Hanif Putra; Permana, Dhias Fajar Widya; Suciati, Nur; Gulsirirat, Preeyaporn (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
The purpose of this study was to analyze the motion of long-distance drive in woodball athletes. The method in this study using quantitative descriptive using observation by Video Recording. The total sample used in this study 8 woodball athletes Semarang State University and all of them were willing to participate in the study by signing the informed consent form. This study uses data analysis techniques using the Kinovea application software Version 0.8.15. The results found that the preparation phase obtaining appropriate criteria, with an average score of 4. The prefix phase in this movement was of 3.8 with appropriate criteria and the implementation phase of 3.7 with appropriate criteria. The follow-through phase obtained an average score of 3.4 with almost appropriate criteria. Overall, the average in the motion analysis is 3.7 with the appropriate category. The conclusion of this study found that motion analysis of long-distance drive in woodball athletes are in the appropriate category. This study also showed quite effective and quite efficient based on the video analysis used. The limitation in this study still focuses on the kinetic data. Future research is expected to improve the quality of the drive and also minimize the occurrence of injuries.